2022
DOI: 10.1073/pnas.2120241119
|View full text |Cite
|
Sign up to set email alerts
|

Long-term preservation of Hadean protocrust in Earth’s mantle

Abstract: Significance Due to active plate tectonics, there are no direct rock archives covering the first ca. 500 million y of Earth’s history. Therefore, insights into Hadean geodynamics rely on indirect observations from geochemistry. We present a high-precision 182 W dataset for rocks from the Kaapvaal Craton, southern Africa, revealing the presence of Hadean protocrustal remnants in Earth’s mantle. This has broad implications for geochemists, geophysicists, and modeler… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 104 publications
4
23
1
Order By: Relevance
“…In-house rock reference material LP 1 is a historical OIB from La Palma (erupted 1480), AGC 351 is a 3455 Ma old granitic gneiss from the Kaapvaal Craton, Southern Africa 45 and 160245 is a 3270 Ma old Komatiite from the Pilbara Craton, NW Australia 11 . The W isotope composition for Cologne in-house rock reference materials reported in this study overlaps with the long-term average that has previously been obtained to assess the intermediate precision for W isotope composition analysis at University of Cologne (Supplementary Data 2 ) 11 , 40 , 41 .…”
Section: Methodssupporting
confidence: 74%
See 2 more Smart Citations
“…In-house rock reference material LP 1 is a historical OIB from La Palma (erupted 1480), AGC 351 is a 3455 Ma old granitic gneiss from the Kaapvaal Craton, Southern Africa 45 and 160245 is a 3270 Ma old Komatiite from the Pilbara Craton, NW Australia 11 . The W isotope composition for Cologne in-house rock reference materials reported in this study overlaps with the long-term average that has previously been obtained to assess the intermediate precision for W isotope composition analysis at University of Cologne (Supplementary Data 2 ) 11 , 40 , 41 .…”
Section: Methodssupporting
confidence: 74%
“…All studied Temagami BIF samples show positive 182 W offsets up to ~8 ppm compared to the inferred modern BSE value, suggesting an average positive µ 182 W signature of the total global W flux into the ocean at 2.7 Ga. With the exception of samples from the southern African region 14 , 39 , 40 , previously studied Archean rocks, irrespective of rock type, are characterized by positive µ 182 W compositions 4 , 5 , 12 , 13 , 41 (Supplementary Fig. 1 ).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Conversely, only samples with MORB-like W/Th may preserve the W isotope composition of their original magmatic source. Within the μ 182 W data set from the Kaapvaal Craton, only four samples exhibit MORB-like W/Th ratios (Tusch et al, 2022;this study). None of these samples show clearly resolvable W isotope anomalies (average μ 182 W = −2.2 ± 2.4), indicating that negative μ 182 W values are not intrinsic to the magmatic sources of analyzed volcanic rocks of the Craton.…”
Section: The Tungsten Budget Of Volcanic Rocks From the Kaapvaal And ...mentioning
confidence: 74%
“…Mundl et al 2017;Willbold et al 2011) has been suggested to imply inefficient mixing between Earth and the moon-forming impactor and, hence, speak against a planetary-mass impactor. However, the small 182 W deficits identified in modern deep-seated mantle plumes are thought to reflect interaction with Earth's core whereas the 182 W excesses measured in Archean rocks (Mundl-Petermeier et al 2020;Rizo et al 2019) are interpreted to reflect the composition of Earth's mantle prior to the addition of the late veneer (Willbold et al 2011;Tusch et al 2021). As such, the preservation of 182 W heterogeneities in Earth's deep mantle does not provide evidence for limited mixing during the moon-forming impact.…”
Section: Discussionmentioning
confidence: 99%